Pengaruh pelayanan prima dan kepuasan terhadap loyalitas pelanggan pada industri perhotelan berbintang di Kota Jambi - Hendriyaldi, Hendriyaldi (Jurnal Paradigma Ekonomika, 2024)
In the digitalization era, every company is expected to be able to solve the problems faced by consumers quickly and based on technology so that they can compete with competitors in facing the era of industrial revolution 4.0. In the hotel industry, good service quality and customer satisfaction have an important role in building customer loyalty. Aims to analyze the influence of excellent service on customer loyalty, the influence of customer satisfaction on customer loyalty and excellent service and customer satisfaction together on customer loyalty in star hotels in Jambi City. This research uses quantitative descriptive research. In this research, researchers collected data to test the hypothesis and multiple linearity regression analysis, and F test and t test. The research results show that excellent service has a positive effect on customer loyalty. Customer satisfaction has a positive effect on customer loyalty and excellent service and customer satisfaction together have a positive effect on customer loyalty, which shows that to increase customer loyalty, excellent service quality and customer satisfaction must also be improved.